Radioligands for imaging myocardial α- and β-adrenoceptors - Riemann, B.; Schäfers, M.; Law, M. P.; Wichter, T.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2003)
Alpha- and beta-adrenoceptors play an important role in the control of heart function. According to their molecular, biological, and pharmacological characteristics, they are subdivided into α1-, α2- and β1-, β2-, β3-, β4-adrenoceptors. In cardiac disease, there is often a selective downregulation of β1-adrenoceptors associated with a relative increase in β2- and α1-adrenoceptors. Functional imaging techniques like single-photon emission tomography (SPECT) and positron emission tomography (PET) provide the unique capability for non-invasive assessment of cardiac adrenoceptors. Radioligands with high specific binding to cardiac α- and β-adrenoceptors suitable for radiolabelling are required for clinical studies. The non-selective β-adrenoceptor antagonist [11C]CGP-12177 was used to quantify β-adrenoceptor density using PET in patients with heart disease. New non-selective ligands (e. g. [11C]CGP-12388, [18F]CGP-12388, [11C]carazolol and [18F]fluorocarazolol) are currently evaluated; β1-selective radioligands (e. g. [11C]CGP-26505, [11C]bisoprolol, [11C]HX-CH 44) and β2-selective radioligands (e. g. [11C]formoterol, [11C]ICI-118551) were assessed in animals. None of them turned out as suitable for cardiac PET.Potential radioligands for imaging cardiac α1-adrenoceptors are based on prazosin. Whereas [11C]prazosin shows low specific binding to myocardium, its derivative [11C]GB67 looks more promising. The putative α2-adrenoceptor radioligand [11C]MK-912 shows high uptake in rodent myocardium but has not yet been evaluated in man.A number of radioligands were evaluated for assessing cardiac adrenoceptors using PET. New radioligands are needed to provide more insight into cardiac pathophysiology which may influence the therapeutic management of patients with cardiovascular disease.
Keywords: Adrenoceptors; myocardium; PET